RANCANG BANGUN APLIKASI POINT OF SALE TIKET BUS PADA PT PRIMAJASA PERDANARAYAUTAMA - Euis Nur Aisyah; Abdul Hayat; Ahmad Ajie Sajidin (LPPM Unbaja, 2019)
The use of information technology in the business world is currently developing very rapidly.One example is the implementation of the Point Of Sale system for selling products that are doneoffline (visiting stores). In the field of transportation, such as modal buses, not all companies canprovide online ticket booking systems to customers. This is usually influenced by the location ofticket sales, as in the case of PT Primajasa perdanarayautama. The company does not provide anonline ordering system for those located at Soekarno Hatta Airport, because the mode busesprovided by this company are used as a link to aircraft transportation. This is due to the worry ofdisrupting the scheduled departure or arrival of airplanes. Although ticket sales at each counterhave used a desktop-based application system, this application cannot produce financial reports.In addition, the existing application is not interconnected between the counters. This makes itdifficult to process financial statements and often cause human error. To overcome this problem,a website-based POS MODA application is created. The research method is carried out throughseveral stages starting from planning, system analysis, system design, and finally the results ofthe system display. The purpose of making this POS MODA application is to be able to speed upthe service process of ticket sales transactions to customers, generate financial reports directly,and the finance department can monitor financial transactions that enter anywhere and anytime.